2022
DOI: 10.1128/jb.00105-22
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subcellular Localization of a Type I CRISPR Complex and the Cas3 Nuclease in Bacteria

Abstract: CRISPR-Cas systems, the prokaryotic adaptive immune systems, are largely understood using structural biology, biochemistry, and genetics. How CRISPR-Cas effectors are organized within cells is currently not well understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This result contrasts with the expression of the Type II-nuclease dead Cas9 CRISPRi systems in different bacteria, where the expression must be fine tuned to prevent toxicity, even when using a non-targeting gRNA ( 77 79 ). While the expression of foreign proteins alone may be impacting bacterial fitness, this result does not exclude the possibility that the Cascade proteins are still non-specifically associated with the DNA during the search for a PAM and target sequence, as is seen by different Type I CRISPR systems in other bacteria ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 95%
“…This result contrasts with the expression of the Type II-nuclease dead Cas9 CRISPRi systems in different bacteria, where the expression must be fine tuned to prevent toxicity, even when using a non-targeting gRNA ( 77 79 ). While the expression of foreign proteins alone may be impacting bacterial fitness, this result does not exclude the possibility that the Cascade proteins are still non-specifically associated with the DNA during the search for a PAM and target sequence, as is seen by different Type I CRISPR systems in other bacteria ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 95%
“…S2). The coexistence of the protospacer with the cognate spacer has been proposed as representing autoimmunity processes with a negative effect on the bacterium ( 37 ), although this may also be explained by the fact that the prophage is expressing anti-CRISPR systems ( 38 ). However, other studies have shown that CRISPR-Cas systems can prevent the lytic cycle of phages but tolerate the virus integration as a prophage, allowing the bacteria to co-opt the phage genes for possible use as virulence factors ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…S1). The coexistence of the protospacer with the cognate spacer has been proposed as representing autoimmunity processes with a negative effect on the bacterium (61), although this may also be explained by the fact that the prophage is expressing anti-CRISPR systems (62). However, other studies have shown that CRISPR-Cas systems can prevent the lytic cycle of phages but tolerate the virus integration as a prophage, allowing the bacteria to co-opt the phage genes for possible use as virulence factors (63).…”
Section: Discussionmentioning
confidence: 99%